Diabetic Retinopathy among Diabetic Patients at a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Pradeep Bastola; Saurav Khatiwada; Mandira Khadka; Polina Dahal; Sheeksha Bastola (Journal of Nepal Medical Association, 2022)
Introduction: The alarming rise in the prevalence of diabetes mellitus is a global public health and economic problem. Diabetic retinopathy is the most common ocular morbidity in the diabetic population and is the leading cause of blindness among the working-age group. This study was aimed to find out the prevalence of diabetic retinopathy in diabetic patients attending to the department of ophthalmology of a tertiary care hospital.